SIMULATION OF VARIATIONAL QUANTUM EIGENSOLVER FOR GROUND STATE ENERGY AND POTENTIAL ENERGY SURFACE CALCULATIONS OF THE HYDRAZINE MOLECULE - Gomosma, Godwin
The total energy calculation using the Variational Quantum Eigensolver (VQE) algorithm has been performed to investigate the potential surface energy and single point energy of the Hydrazine molecule and its conformations. Three types of basis sets were used, and the Unitary Coupled Cluster Single-Double Excitation (UCCSD) Ansatz was chosen. The VQE application in this thesis also utilizes the active space approach for the UCCSD Ansatz, selecting active spaces (2,2) and (4,4) around the Frontier Orbitals. The VQE algorithm was implemented using a classical simulator provided by the Qiskit module, an open-source module developed by IBM for designing and executing quantum computations. The calculation results from the VQE method were then compared with classical calculation methods (MP2, CASSCF with active spaces (2,2) and (4,4), CCSD(T), and QCISD(T)). All classical calculation methods were performed using the Gaussian 09 software. The geometry and coordinates of the hydrazine molecule were optimized using the MP2 method based on the 6-31+G(d,p), 6-31G(d), and 6-311G(d,p) basis sets, which were then used as reference geometries for performing single point energy calculations and potential surface energy simulations for each of these basis sets. The implementation of the VQE method in evaluating the energy of the hydrazine molecule showed results consistent with theory and classical calculation methods. Enlarging the active space from (2,2) to (4,4) in the UCCSD Ansatz did not significantly change the ground state energy, unlike CASSCF, which is more sensitive to changes in the active space. The ground state energy value from VQE was still higher compared to classical methods like CCSD(T). However, in potential surface energy calculations, VQE showed results consistent with MP2 and CCSD(T), demonstrating VQE with the UCCSD Ansatz's ability to evaluate energy related to structural changes and effectively capture electron interactions.